Association of GCK (rs1799884), GCKR (rs780094), and G6PC2 (rs560887) Gene Polymorphisms with Type 2 Diabetes among Malay Ethnics - Ansari, Neda; Ramachandran, Vasudevan; Mohamad, Nur Afiqah; Salim, Elnaz; Ismail, Patimah; Hazmi, Mohamad; Mat, Liyana Najwa Inchee (Global Medical Genetics, 2023)
Background Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder, and the underlying causes remain unknown and have not been fully elucidated. Several candidate genes have been associated with T2DM in various populations with conflicting results. The variations found in glucokinase (GCK), glucokinase regulatory protein (GCKR), and glucose-6-phosphatase 2 (G6PC2) genes were not well studied, particularly among Asians.Aims The main objective of this study was to determine the candidate genetic polymorphisms of GCK (rs1799884), GCKR (rs780094), and G6PC2 (rs560887) genes in T2DM among Malay ethnics.Methods In this candidate gene association study, a total of 180 T2DM subjects and 180 control subjects were recruited to determine the genotypes using polymerase chain reaction-restriction fragment length polymorphism and Taqman probe assay methods. Genotype and allele frequencies in case and control samples were compared using the chi-squared test to determine a significant difference.Results The body mass index, fasting blood glucose, hemoglobin A1c, systolic and diastolic blood pressure, and total cholesterol were significantly different (p < 0.05) between T2DM and control subjects. The genotypic and allelic frequencies of GCK (rs1799884), GCKR (rs780094), and G6PC2 (rs560887) gene polymorphisms were significantly different between T2DM and controls (p < 0.05).Conclusion Hence, rs1799884 of GCK gene and rs780094 of GCKR gene and rs560887 of the G6PC2 gene are possible genetic biomarkers in T2DM development among Malay ethnics in Malaysia.
Keywords: GCK gene polymorphism; diabetes; biomarkers; Malay ethnics